Die goedkeuring van kerkrade vir 'n nuwe verband in die NG Kerkfamilie? - Strauss, P. J. (Faculty of Theology, University of the Free State, 1999)
This article probes the question of which assembly within a reformed church denomination - in this case the family of Dutch Reformed Churches - should have the jurisdiction in deciding on the alteration of the confession(s) and especially, the constitution and contents of this denomination. The conclusion is a fairly simple one. If it is accepted that che congregation, as governed by consistories, is a fully fledged church and that congregations constitute a specific denomination, then the consistories involved should decide the matter. Congregations should be able to give their consent co the new denomination they enter into. On che one hand the undefined and general structural unity of rhe church, is a Biblical principle. On the ocher hand, the formulation and constitution of confessions and specific denominations is a matter for the believers within a certain historical concext. They should also be able to enter into a structure of church unity willingly and in the belief - because the church is an institution of faith - that it is the will of God.

Hierdie artikel gaan in op die vraag watter vergadering(s) binne gereformeerde kerkverband die bevoegdheid moet hê om oor die verandering van die belydenisskrifte en die samestelling en inhoud van die kerkverband te besluit. Die geval van die Nederduitse Gereformeerde Kerkfamilie word spesifiek ondersoek. Die artikel kom tot 'n redelike eenvoudige gevolgtrekking. As dit aanvaar word dat gemeentes - onder die opsig en tug van kerkrade - volledig kerk is, en dat gemeentes 'n kerkverband vorm, moet kerkrade oor die belydenis en aard van die kerkvervand waartoe hulle toetree, besluit. Die sigbare eenheid van die kerk is enersyds 'n nie-gedetailleerde, algemeen Bybelse beginsel. Aan die ander kant geskied die formulering van 'n spesifieke belydenis en die strukturering van 'n spesifieke kerkverband ook altyd binne 'n bepaalde historiese konteks. Hiertoe moet die gelowiges (gemeentes) gewillig én met die oortuiging dat dit Gods wil is, kan toetree.
Keywords: Confessions; New denomination; Congregations